Results of in vitro chemotherapy of apple cv. Fragrance - Short communication - F. Paprštein; J. Sedlák; L. Svobodová; J. Polák; S. Gadiou (Horticultural Science, 2013)
The effect of the chemotherapy with ribavirin on the elimination of the pome fruit viruses from in vitro grown plants of infected apple cv. Fragnance has been investigated. The results of ELISA and RT-PCR testing proved the presence of mixed infection of Apple stem pitting virus (ASPV), Apple chlorotic leaf spot virus (ACLSV) and Apple stem grooving virus (ASGV) in the initial field-grown tree of this apple cultivar. Obtained actively growing in vitro shoots with well-developed leaves and shoot tips were subsequently used for chemotherapy with ribavirin. Attempts to fully eliminate viruses by ribavirin in lower concentration 20 mg/l were not successful. However in vitro plants of one mericlone (FR1R20) sanitated from ASPV and ASGV, which were infected with ACLSV only after the first chemotherapy cycle, were subjected to repeated treatment on medium with higher ribavirin concentration 100 mg/l. The success of chemotherapy with ribavirin at 100 mg/l was 76% for ACLSV elimination after the second round. In the course of both chemotherapy cycles (20 mg/l and 100 mg/l), in vitro plants did not display symptoms of phytotoxicity.